A Study of the Relationship between Job Satisfaction and Burnout among Neonatal Intensive Care Unit Staff - Reza Saeidi; Azra Izanloo; Sara Izanlou (Mashhad University of Medical Sciences, 2020)
Background: Considering the importance of job satisfaction and occupational burnout among nurses, the present study aimed to determine the prevalence of occupational burnout and the degree of job satisfaction among neonatal intensive care unit (NICU) nurses. Methods: The current research was a cross-sectional study in which the Job Descriptive Index and Maslach Burnout Inventory were distributed among the NICU nurses. The collected data were analyzed using SPSS software. Results: A total of 30 NICU nurses working in two public and private hospitals participated in the present study. The mean age of the participants was measured at 37.46±6.93 years, most of them (73.3%) held a Bachelor's degree and more than 60% were married. No significant relationship between job satisfaction and burnout was observed among the nurses. Both variables were moderate among the NICU nurses as representatives of the staff working in special units. Conclusion: It is widely believed that people who are exposed to extreme stress for a long time are more likely to suffer from occupational burnout. Moreover, considering the importance of this issue in healthcare environments for the provision of services that physically and mentally affect patients, it is recommended to pay greater attention to employee satisfaction and burnout process in hospital settings.